Implied adjusted volatility functions: empirical evidence from Australian index option market - Harun, Hanani Farhah; Abdullah, Mimi Hafizah (2014)

(untitled)
With the implied volatility as a significant aspect particularly in option valuation, and given the fact that the pricing biases of Leland option pricing models and the implied volatility structure of the option are related, this study primarily aims to investigate the implied adjusted volatility functions using different Leland option pricing models and to assess whether the use of the specified implied adjusted volatility function can lead to an improvement in option valuation accuracy. The implied adjusted volatility is investigated in the context of Standard and Poor/Australian Stock Exchange (S&P/ASX) 200 index options over the course of 2001-2010, which covers the global financial crisis in the mid-2007 until the end of 2008. Both in- and out-of-sample resulted in approximately similar pricing error along the different Leland’s models. Results indicate that symmetric and asymmetric models of both moneyness ratio and logarithmic transformation of moneyness provide the overall best result in both during and post-crisis periods, respectively. We find that in the different period of interval (pre-, during and post-crisis) is subject to a different implied adjusted volatility function which best explains the index options. Hence, it is tremendously important to identify the intervals beforehand in investigating the implied adjusted volatility function.